DETERMINANTS OF SUCCESSFUL INTERNALIZATION OF RELIGIOUS MODERATION IN CHARACTER EDUCATION AT THE PRIMARY SCHOOL LEVEL: A SYSTEMATIC LITERATURE REVIEW - Junaidi; Rohmani Rohmani (International Journal of Multidisciplinary Reseach, 2026)
Background and Purpose: The successful internalization of religious moderation within primary school character education constitutes a multidimensional and contextually embedded process of critical importance for fostering tolerance and social cohesion in pluralistic societies. Despite growing scholarly interest, a rigorous synthesis of the factors determining this success remains absent. This systematic literature review (SLR) aims to identify, critically analyze, and synthesize the key determinants of successful religious moderation internalization in primary school character education programs. Methods: Following the PRISMA 2020 guidelines, a systematic search of the Scopus database was conducted using Boolean operators combining the terms